Null Effect of Olfactory Training With Patients Suffering From Depressive Disorders—An Exploratory Randomized Controlled Clinical Trial - Pabel, Luise D. (Front Psychiatry, 2020)
Due to a close functional relation between brain areas processing emotion and those processing olfaction, major depression is often accompanied by reduced olfactory function. Such hyposmia can be improved by regular olfactory training (OT) over several months. As this training furthermore improves subjective well-being, we explored whether OT is a useful complementary strategy for depression treatment. A total of 102 depressive outpatients were randomly assigned to OT or a control training condition, which were performed twice a day for 16 weeks. Compliance was continuously monitored. Before and after training we measured depression severity and olfactory function. About half of the patients of both groups did not complete the training. Among the remaining patients, depression severity decreased significantly in both groups. The absence of an interaction effect indicated no selective impact of OT and the variance of depression improvement explained by OT was as little as 0.1%. The low compliance suggests that OT is not feasible for large parts of our sample of depressive outpatients, most likely due to a disease-immanent lack of motivation. In those patients who completed the training, lack of specific effects suggest that OT is not more useful then unspecific activation or attention training. CLINICAL TRIAL REGISTRATION: This clinical trial was registered at German Registry for Clinical Trials (DRKS), main ID: DRKS00016350, URL: http://www.drks.de/DRKS00016350.